Hubungan pengetahuan kegawatan trauma olahraga dengan penggunaan body protector pada anggota komunitas pencak silat - Nur Aini, Dwi Miftia (Jurnal Keperawatan Muhammadiyah, 2025)
ABSTRACT Nur Aini, Dwi Miftia . 2025. The Relationship BetweenKnowledge of Sports Trauma Emergencies andthe Use of Body Protectors Among Members ofthe Pencak Silat Community in Bojonegoro.Undergraduate Thesis. Nursing Study Program. Universitas Muhammadiyah Lamongan. Advisors (1)Isni Lailatul Maghfiroh, S.Kep., Ns., M.Kep (2) Inta Susanti, S.Kep., Ns., M.kep Sports-related trauma is a common risk in pencak silatpractice. The use of personal protective equipment (body protectors) is crucial in preventing trauma and mitigating the severity of sports injuries. This study aimed to examine the relationship between knowledge of sports trauma emergencies and the use of body protectors among members of pencak silatcommunities in Bojonegoro City. This correlational analytic research employed a cross-sectional approach. A total of 90 respondents were selected from the three largest pencak silatcommunities in Bojonegoro using a cluster sampling technique. The instruments included a sports trauma emergency knowledge questionnaire and an observation checklist for body protector use. Data were analyzed using the Spearman test. Results showed that 47.8% of respondents had good knowledge of sports trauma emergencies. Moreover, 43.33% of respondents reported complete use of body protectors, while 30% used them incompletely. Statistical analysis revealed a significant relationship between knowledge and the use of body protectors (p = 0.000, r = 0.391). Although the correlation strength was relatively weak, the findings highlight knowledge as a prerequisite for safe behavior. Knowledge of sports trauma emergencies influences the use of protective equipment. These results align with previous research that identifies knowledge, safety, and comfort as key determinants of compliance with protective gear use. Adequate understanding of trauma severity raises awareness and motivates pencak silat practitioners to wear body protectors during training. Therefore, improving knowledge of body protector use is essential to enhancing practitioner safety. Keywords: Body Protector, Knowledge, Pencak Silat, Trauma